Sustainability of the Macedonian Current Account - Danica Unevska; Branimir Jovanovic (National Bank of the Republic of Macedonia, 2011)
Most of the emerging European countries, including Republic of Macedonia, are faced with greater or smaller current account deficits, which raise the concern about their sustainability in the long run. This working paper examines the sustainability of the Macedonian current account deficit using the structural model of the current account. According to this model, the current account is viewed as the outcome of variations in macroeconomic "structural" determinants that influence the saving-investment balance. The results show that budget deficit, economic growth, FDI and financial intermediation are the variables that had an effect on the Macedonian current account in the period 1998-2009, and that the sustainable level of the current account deficit is in the range of 5.3%-9.1% of GDP. The current account deficit was fluctuating around this sustainable level most of the time, which indicates that external equilibrium was not jeopardized. However, in the period between the last quarter of 2007 and the first quarter of 2009, due to the two external shocks in this period (the global increase of prices and the global recession), the current account deficit was higher than the sustainable level, which suggested a violation of the external equilibrium. Although the equilibrium was restored later in 2009, this historical episode points out the need for structural reforms in the Macedonian economy in order to avoid repeating such episodes in the future.
Keywords: F32; F37; 330; current account; sustainability; structural model; saving and investment; external equilibrium; Macedonia